The influx of orthophosphate into squid giant axons - Caldwell, P. C. (1970)
1. The influx of (32)P, applied externally as orthophosphate, into the axoplasm of squid giant axons has been studied. 2. An average orthophosphate influx of 20·9 f-mole/cm(2).sec is obtained if the (32)P found in the axoplasm is assumed to be indicative of orthophosphate which has crossed the axolemma. 3. The influx does not show very much dependence on external orthophosphate concentration in the range 0·02-0·5 mM. 4. The influx is reduced by cyanide, 2,4-dinitrophenol, ouabain and by the absence of external potassium. 5. The (32)P appears to arrive in the axoplasm as orthophosphate. 6. It is concluded that there is an inward movement of orthophosphate into the axons which is mediated by an active transport process and that this may have some connexion with the active transport of sodium and potassium.